RAMAN IMAGING OF DENTAL FOLLICLE MESENCHYMAL STEM CELLS - LEOPOLD, Loredana F.; COMAN, Cristina; TODOR, Istvan Sz.; SZABO, Laszlo; SORIȚĂU, Olga; VIRAG, Piroska; MIHU, Carmen M.; MOISOIU, Vlad; LEOPOLD, Nicolae (Studia Universitatis Babeș-Bolyai Physica, 2015)
Raman spectroscopy is slowly but surely becoming an important investigative method in cellular samples. In this study, the potential of Raman mapping was assessed on dental follicle mesenchymal stem cells (MSCs). Raman spectra were recorded with the 532 nm laser line at ~1 mm spatial resolution. Principal Component Analysis (PCA) of the recorded Raman spectra provided false color Raman maps, evidencing cellular components such as the nucleus, nucleolus, endoplasmic reticulum and cytoplasmic RNA. A high concentration of this last component can be considered as a universal marker for stem cells. Given that stem cells are in a state where they are always ready to undergo transcription, a large concentration of RNA is found in the cytoplasm of these cells, as they rapidly need to produce proteins that specialize the cell during differentiation.